γH2AX expression in cytological specimens as a biomarker of response to radiotherapy in solid malignancies - Shah, K; Boghozian, R; Kartsonaki, C; Shah, K; Vallis, K (Wiley, 2015)
Many anticancer treatments, including radiotherapy, act by damaging DNA and hindering cell function and proliferation. H2AX is a histone protein directly associated with DNA that is phosphorylated to produce γH2AX that accumulates in foci in an early response to DNA double-strand breaks, the most deleterious lesion caused by anticancer therapy. This study reports a γH2AX detection assay that has the potential to be used as a biomarker of response to guide cancer treatment. γH2AX immunostaining was applied to tumour cell specimens obtained using fine needle aspiration (FNA). Liquid-based cytology and direct smear cytology methods were evaluated and immunostaining protocols established using FNA samples from five cancer patients. The assay was then applied to three patients before and after radiotherapy. Results demonstrate induction of γH2AX foci following treatment, persisting for as long as one week after therapy. Immunostaining for γH2AX has been successfully applied to FNA samples, providing an opportunity to evaluate γH2AX as a treatment response marker in cancer. Diagn. Cytopathol. 2016;44:141-146. © 2015 Wiley Periodicals, Inc.